PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA OUTDOOR TERHADAP KOMPETENSI PENGETAHUAN IPA KELAS V - Ni Luh Eri Kumala Dewi (Journal for Lesson and Learning Studies, 2018)
This research’s aims to know the significant difference of science competence between the group students with the Project Based Learning model assisted by outdoor media companed to group of students conventional method for fifth grade students of SD Gugus II in North Kuta academic year of 2017/2018. This research is an experiment with the research design used is  non-equivalent control group design. The populations of this research are all of the students of fifth grade which amount 334 students. The sample is determined by random sampling technique. The sample is students of fifth grade A in  SD Number  1 Tibubeneng totaled 39 students as the experimental group and students of fifth grade A in SD Number 2 Tibubeneng totaled 33 students as the control group. Data collection technique using testing technique by objective test type multiple choice regular. Technique data abalysis using the t test. The results showed that tcount = 3,890 and at significance level 5% and dk = 70 obtained ttable = 2,000 sehingga tcount = 3,890 > ttable = 2,000. Based on the criteria  for testing, then H0  is rejected and Ha is accepted. The velue of science competence group with the Project Based Learning model assisted by outdoor media is  82,18, and group of students with the conventional method is 75,76. Based on these result Project Based Learning model assisted by outdoor media environment affect the science competence fifth grade students of SD Gugus II North Kuta academic year of 2017/2018.